A new species of Dicrotendipes (Diptera: Chironomidae) from Florida - Epler, J.h. (Zootaxa, 2016)
A new species of Dicrotendipes is described in all life stages from Florida. Adults of this new species are nearly identical to D. modestus (Say); pupae are similar to D. modestus, D. neomodestus (Malloch) and D. tritomus (Kieffer); while the larvae are unique and were keyed by Epler (1992, 1995, 2001) as Dicrotendipes sp. A. The taxonomic status of D. modestus and D. pulsus (Walker) is discussed.